Manajemen Kurikulum Yanbu’a Dalam Pembelajaran Mengaji Dan Menghafal Al-Qur’an - Khusnurridlo Ar, Moh; Badri; Fadhurrosi (Tarunaedu: Journal of Education and Learning, 2025)
This study aims to examine comprehensively the curriculum management of Yanbu’a in Qur’anic learning at Pondok Pesantren Nurul Islam Kapongan Situbondo, focusing on planning, implementation, evaluation, and its contribution to the formation of Qur’anic character. Employing a qualitative narrative approach, the research involved purposively selected participants, including pesantren leaders, Yanbu’a program managers, teachers, students, and parents. Data were collected through observation, in-depth interviews, and documentation, and analyzed interactively using Miles and Huberman’s model. The findings reveal that the Yanbu’a curriculum is designed adaptively and contextually, emphasizing gradual mastery, quality recitation, and spiritual habituation rather than rigid memorization targets. Its implementation integrates multimodal strategies (visual, auditory, and talaqqi wa musyafahah), daily routines, and structured evaluation based on individual competency achievements. The curriculum contributes significantly to producing students who are fluent in Qur’anic recitation, systematic in memorization, and disciplined in character. However, challenges such as limited time allocation, large class sizes, and teacher consistency were identified as barriers to optimal outcomes. This research concludes that Yanbu’a represents not only a technical learning method but also a holistic Qur’anic educational system embedded in pesantren values. It is recommended that future development focus on strengthening class management, improving teacher competence through continuous training, enhancing post-graduation programs, and expanding parent involvement to ensure sustainable Qur’anic education.